Peningkatan keterampilan sosial komunikasi melalui model creative problem solving(CPS) dalam pembelajaran IPS di sekolah dasar - Eri Nugraheni; Hadi Mulyono; Hadiyah Hadiyah (Universitas Sebelas Maret, 2022)
. This research aims to improve social communication skills through creative problem solving models in social education science learning. This research is a Class Action Research with research subjects of grade 4 students of SD Negeri Sibela Barat No.251 Surakarta Academic Year 2019/2020 which amounts to 16 students and the object of research is social communication skills in social studies lessons. Data collection techniques in the form of observation, interviews, tests, and document analysis. validity of the content. The data analysis used is Miles-Huberman's interactive analysis model. The average yield on pre-action was 65.62 with a skilled category of 25%. Then in the first cycle the average value increased to 75 with a skilled category of 56.25&. Then in the second cycle the average value reaches 81.25. skilled category of 87.5%. Based on the results of the research, it can be concluded that the ability of social communication skills in IPS learning can be strengthened through creative problem solving models. This research is expected to be a reference and development both in learning and similar research.